PHOTOREACTIVATION IN VITRO OF ULTRAVIOLET INACTIVATED HEMOPHILUS INFLUENZAE TRANSFORMING FACTOR - Rupert, Claud S. (The Rockefeller University Press, 1958)
Hemophilus influenzae—transforming DNA, which has been inactivated by ultra-violet radiation, is reactivated by visible light in the presence of a cell-free extract of Escherichia coli B. The time rate of reactivation is increased by increasing the E. coli extract concentration, the temperature, and the intensity of illumination. Only DNA containing an ultraviolet-damaged genetic marker exhibits increased transforming activity after treatment with the photoreactivating system. The reactivating capacity of the extract remains in the top supernatant after centrifugation at 110,000 x g for 1 hour and is not present in the pellet. This capacity is destroyed by heating to 90°C. for 1 minute. The active system of the E. coli extract is separable into dialyzable, heat-stable and non-dialyzable, heat-labile fractions. The dialyzable fraction contains at least one component which limits the maximum degree of recovery attained.